Pengaruh Karakteristik Perusahaan dan Corporate Governance terhadap Praktik Publikasi Sustainability Report pada Perusahaan Publik di Indonesia - Tumewu, James (Universitas Pakuan, 2017)
Publication of sustainability report (SR) in Indonesia is still voluntary, but the interests and priorities of the company to publish SR increases. The aim of this research is to examine the effects of profitability, liquidity, leverage, activity ratio, total assets, number of employees, capital structure, the number of audit committee meetings, the number of board meetings, and governance committee to the publication of sustainability report (SR). The population of this research is listed companies in the Indonesia Stock Exchange (IDX) in the year 2007-2010. The selection of this sample uses purposive sampling method. Based on purposive sampling method, the samples of firms that publish sustainability report (SR) are 24 companies while the number of companies that do not publish sustainability report (SR) are 19 companies. The analysis tool to test the hypothesis is the discriminant analysis. Results of this research indicate that total assets, number of employees, board meetings, and committee governance have a positive effect on publication of SR. The leverage indicates a negative effect on publication of SR. While return on assets, current ratio, inventory turnover, capital structure, audit committee meetings showed no effect on SR publications.Â